Prognostic value of right ventricular dysfunction in aortic regurgitation after transcatheter aortic valve replacement - Mao, Yu; Liu, Yang; Zhai, Mengen; Jin, Ping; Zhang, Haibo; Wei, Lai; Shang, Xiaoke; Guo, Yingqiang; Pan, Xiangbin; Yang, Jian (Frontiers in Cardiovascular Medicine, 2024)
Background Aortic regurgitation (AR) may lead to right ventricular dysfunction (RVD), but the prognostic value of RVD in patients undergoing transcatheter aortic valve replacement (TAVR) remains unclear. Our goal was to evaluate the clinical implications, predictors and prognostic significance of RVD in patients with pure AR after TAVR. Methods In this multicentre prospective study, patients undergoing TAVR were included between January 2019 and April 2021. The patients were divided into four groups according to the results of transthoracic echocardiography pre- and post-TAVR. The primary end point was 2-year all-cause mortality. Results A total of 648 patients were divided into four groups: 325 patients (54.3%) in the no RVD group; 106 patients (17.7%) in the new-onset RVD group; 73 patients (12.2%) in the normalized RVD group; and 94 patients (15.7%) in the residual RVD group. At the 2-year follow-up, there were significant differences in all-cause mortality among the four groups (5.2%, 12.3%, 11.0% and 17.0%, respectively; p < 0.05). New-onset RVD was correlated with an increased risk of all-cause death and a composite end point and normalized RVD improved clinical outcomes of baseline RVD. Predictors of new-onset RVD included a higher Society of Thoracic Surgeons score, larger left ventricular end-diastolic volume, lower left ventricular ejection fraction, higher systolic pulmonary artery pressure and smaller RV base diameter. Conclusions Changes in periprocedural RVD status significantly affect the risk stratification outcomes after TAVR. Therefore, they may be used as part of decision-making and risk assessment strategies.